2018
DOI: 10.1097/meg.0000000000001004
|View full text |Cite
|
Sign up to set email alerts
|

De-novo versus recurrent hepatocellular carcinoma following direct-acting antiviral therapy for hepatitis C virus

Abstract: Although de-novo HCC lesions significantly developed later than recurrent lesions in DAAs-treated patients, their response rates were significantly better. No differences were detected between both groups in their response to DAAs and their tumoral characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Overall, 24 papers (with 25 cohorts of patients) [6,7, reporting on HCC recurrence after DAAs treatment in patients with previously and successfully treated HCC (liver resection, ablation or trans-catheter arterial chemoembolization -TACE) were identified. Two papers only considered patients with HCC recurrence [25,27], two included also patients who underwent liver transplantation before starting DAAs [16,29], and one focused on radiological features of…”
Section: Literature Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 24 papers (with 25 cohorts of patients) [6,7, reporting on HCC recurrence after DAAs treatment in patients with previously and successfully treated HCC (liver resection, ablation or trans-catheter arterial chemoembolization -TACE) were identified. Two papers only considered patients with HCC recurrence [25,27], two included also patients who underwent liver transplantation before starting DAAs [16,29], and one focused on radiological features of…”
Section: Literature Selectionmentioning
confidence: 99%
“…Some authors speculated about a major aggressiveness of the recurrent tumor in DAAs treated patients [6,10,11,[26][27][28]. However, it should be noted that a definition of HCC aggressiveness does not exist in literature, or at least an agreement on its definition has not been reached as yet.…”
Section: Aggressiveness Of Recurrencesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, achieving SVR with DAAs does not seem to reduce the risk of HCC development [61]. De novo HCC lesions appear to develop significantly later than recurrent lesions in patients treated with DAAs, with response rates that are significantly lower in the latter subjects [62]. Moreover, a casecontrol study on patients with HCV-related HCC reported that HCC behaviour was more aggressive in DAA-treated patients than in non-DAA patients in terms of portal vein thrombosis, malignant lymphadenopathy and HCC imaging characteristics [63].…”
Section: Potential Benefits Potential Harmsmentioning
confidence: 99%